City in Charles Dickens’ Great Expectations and Morteza Moshfeq Kazemi’s Tehran-e Makhuf (The Horrible Tehran): A Comparative Study - Kiana Vakili Robati; Masoud Farahmandfar (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
Setting in literature has long been a prominent issue in literary evaluations. The systematic concern with setting and space dates back to the time Aristotle first discussed the concept of "spectacle" in his Poetics, deeming it essential to the formation of a proper tragedy. Today, spatial studies frequently acknowledge Charles Dickens as one of the greatest observers of the operation of the city in the novel. His foremost novel, Great Expectations, depicts modernity and the social hardships of the time in the form of a love story bringing the plot in close proximity with Morteza Moshfeq Kazemi’s novel Tehran-e Makhuf .This article focuses on the scrutinizing of the creation of social spaces in these two novels through the utilization of Henri Lefebvre’s theory of space as an active production of each society. The concern with space and city and their function is further reflected in the section “City, Space, and Society,," followed in more detail in the section “The City.” In the section “Society, and the Background of the Author,” and the one after, “The Portrayal of the Two Cities and Social Space,” the cities envisioned are observed apropos of the image created, its relationship to the narrative, and social relations. Consequently it is proposed that the cities produced by these two novels are not essentially objects, but rather, the city is a product of that society-- dominating and producing the society itself through its active production by the witnesses,